To *be exist or not to *be exist ? That is the Question - بوهنية, بشير (Revues faculté des lettres et des langues, 2016)
يتمحور هدا البحث حول الاستعمال الخاطئ للفعل يكون من طرف طلبة اللغة الانجليزية من التعليم العالي بجامعة أدرار. يتكون الجزء الأساسي للبحث من أكثر من ألفين ورقة امتحان للسداسي الأول و الثاني لعشر مواسم جامعية. أساس فرضية البحث هو أن الاستعمال الخاطئ للفعل يكون لا ينجم عن الطلبة بل هو ناتج عن  للتدريس الخاطئ لكيفية استعماله في مدارس الطور المتوسط و الثانوي.    This corpus study analyses the wrong use of the verb to exist as *to be exist under various forms and tenses such as *is exists, *are existed, *does not exist, and *existness . The corpus consists of more than two thousand exam copies for the academic years 2003 through 2013 held at the university of Adrar, Department of English.  Error Analysis considers a fault as mistake or error depending on its frequency of repetition and on its over or under-generalisation to the learners. The research contends that this mistake/error is not the learners’ deed, but is taught to them under that erroneous form in intermediate or secondary schools. To substantiate this argument, the survey shows that the wrong verb to *be exist is used by students from different levels (Classical and LMD systems) with different educational and geographical backgrounds.